Gut microecology: effective targets for natural products to modulate uric acid metabolism - Wang, Hui; Zheng, Yixuan; Yang, Mengfan; Wang, Lu; Xu, Yao; You, Siqi; Mao, Nan; Fan, Junming; Ren, Sichong (Frontiers in Pharmacology, 2024)
Gut microecology,the complex community consisting of microorganisms and their microenvironments in the gastrointestinal tract, plays a vital role in maintaining overall health and regulating various physiological and pathological processes. Recent studies have highlighted the significant impact of gut microecology on the regulation of uric acid metabolism. Natural products, including monomers, extracts, and traditional Chinese medicine formulations derived from natural sources such as plants, animals, and microorganisms, have also been investigated for their potential role in modulating uric acid metabolism. According to research, The stability of gut microecology is a crucial link for natural products to maintain healthy uric acid metabolism and reduce hyperuricemia-related diseases. Herein, we review the recent advanced evidence revealing the bidirectional regulation between gut microecology and uric acid metabolism. And separately summarize the key evidence of natural extracts and herbal formulations in regulating both aspects. In addition,we elucidated the important mechanisms of natural products in regulating uric acid metabolism and secondary diseases through gut microecology, especially by modulating the composition of gut microbiota, gut mucosal barrier, inflammatory response, purine catalyzation, and associated transporters.This review may offer a novel insight into uric acid and its associated disorders management and highlight a perspective for exploring its potential therapeutic drugs from natural products.